Communication Patterns of Adolescent Self-Harm Suffering in Interpersonal Relationships - Genny Gustina Sari; Welly Wirman (Jurnal Kajian Komunikasi, 2022)
The phenomenon of self-harm is an iceberg phenomenon that generally attacks teenagers. Self-harm is an act of self-harm in which the perpetrator finds pleasure and a feeling of satisfaction and relief. This act of self-harm is not properly recorded, but the times have shown that self-harm sufferers have begun to show their activities on social media such as Twitter. Several previous studies have explained that teenagers self-harm due to a lack of communication and bonding between the perpetrator and his family and closest people. The purpose of this study was to determine the process of social penetration in adolescents with self-harm communication patterns in establishing interpersonal relationships in Pekanbaru City and to determine the communication patterns formed in adolescents with self-harm in establishing interpersonal relationships with family and friends in Pekanbaru City. This study uses a qualitative research method with a phenomenological approach. Based on the findings in the field, the communication pattern found by self-harm sufferers with their families is using permissive communication patterns. Permissive communication patterns of self-harm sufferers are in the form of indifference, indifference, and freedom that goes beyond parents’ boundaries to children. Self-harm sufferers admit minimal verbal and nonverbal interaction with their parents and that self-harm is done not as a form of protest but rather as an emotional outlet. Self-harm is a form of children’s disappointment with their parents, and their actions upload these actions on Twitter as a form of protest and resistance by children against communication patterns and parenting patterns in a wider scope as well as a medium for dancing with friends so that they don’t feel alone.